Hubungan Antara Telogen Effluvium Dengan Pasien Paska Infeksi Covid-19 Di Rumah Sakit Umum Muhammadiyah Kota Metro Lampung - Andrini, Nita; Fatihin, Ifadatul (ANATOMICA MEDICAL JOURNAL | AMJ, 2024)
Introduction: Covid-19 is a new corona virus that has now spread to human life, more specifically, it was first detected in Wuhan in China and has now reached 196 affected countries. Coronavirus disease 2019 is a disease caused by a virus from the Coronaviridae family called SevereAcuteRespiratory Syndrome Coronavirus-2. The Covid-19 pandemic has caused a profound psychological impact on society as a whole and a long-term sequelae of the disease. Excessive hair loss after Covid-19 can occur in patients and may affect their mental health. The hair cycle is highly susceptible to endogenous and exogenous stimuli, including febrile states and emotional stress, which persist in this era of pandemics. Telogen effluvium is a non-inflammatory disease characterized by diffuse loss of telogen hair, caused by disruption of the hair cycle leading to increased and synchronized telogen release. Methods: This research used a descriptive observational research design with cross-sectional method, which carried out for 1 month, at Muhammadiyah General Hospital Metro City, Lampung. The target population in this study were telogen effluvium sufferers with post-Covid-19 period July 2020 to May 2021, with the sampling technique used was total sampling from medical record data. Results:Based on the Chi Square test, the Fisher's Exact Test Sig value was obtained. (2-sides) is 0.001 (P0.05) which means that there is a significant relationship between the two variables. Decision: There is a relationship between telogen effluvium in post-Covid-19 infection patients at Muhammadiyah General Hospital Metro City, Lampung.